Effect of Using Zornia glochidiata (shelini) Meal in Replacement of Wheat Bran on Lamb Performance and Feeding Cost Decreasing - Idris Adam Idris1; Mohamed Tagi Saed Kiir; Suleiman Eshag Mohamed Abdalla; Salah Basar Hammad Dahia; Jumaa Barram Jadalla; Mohammed Alhadi Ebrahiem (International Journal of Veterinary Science and Research - Peertechz Publications, 2021)
This trial was aimed to study the effects of replacing wheat bran with different levels of Zornia glochidiata meal on feed intake, general performance of Desert lambs and feeding cost decreasing. Twelve lambs of four months old and weighing 19.500 kg +500g were divided into three groups each with four animals. Feed intake and body weight change were monitored every ten days up to fifty days. The data were statistically analyzed via analysis of variance and the differences among means were detected least significance (LSD) test. The results indicated that voluntary dry matter intake significantly (P<0.05) increased in the group that consumed a ration with 26% Zornia glochidiata meal (II) followed by those were on a ration with wheat bran only (I) and lastly that had a ration with 42% Z. glochidiata (III). Feed intake was 1090, 970 and 910 for group II, I and III, respectively. Similarly body weight gain was significantly (P<0.05) higher in group II, (6.1kg/50 days) followed by group I (4.9 kg/50 days) and group III with 4.3 kg/50 days. The daily weight gain was 98, 122, 89 g when the lambs consumed rations with 0.00, 26 and 42 % of Z. glochidiata meal, respectively. The cost of kilogram of the first ration was 6.8 SDG when only wheat bran was used, and it decreased to 5.7 SDG when 26% wheat was replaced by Z. glochidiata meal and when Z. glochidiata meal was increased to 41% the cost was further decreased to 5 SDG.